On the effects of monetary policy shocks on exchange rates - Michael Binder; Qianying Chen; Xuan Zhang (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper we re-consider the effects of monetary policy shocks on exchange rates and forward premia. In the recent empirical literature, these effects have been predominantly described as puzzling, in that they would include delayed overshooting of the exchange rate as well as persistent deviations from uncovered interest parity. We specify an empirical model that in particular (i) allows for simultaneous multi-country adjustments in response to monetary policy shocks, and (ii) takes advantage of the identifying restrictions for monetary policy shocks implied by empirically supported long-run relations between the macroeconomic variables under consideration. Using monthly data from 1978 to 2006 for a panel of nine industrial economies (Australia, Canada, France, Germany, Italy, Japan, New Zealand, United Kingdom, and the United States), we find that U.S. Dollar effective and bilateral real exchange rates appreciate on impact after a contractionary U.S. monetary policy shock, and that there is no delay in the overshooting of the U.S. Dollar. Furthermore, there is no persistent significant forward premium. These results are consistent with the real exchange rate effects of monetary policy shocks in sticky price macroeconomic models, though the results of this paper also suggest that the latter models should be specified so as to capture simultaneous multi-country adjustments to shocks.
Keywords: C33; E52; F31; 330; monetary policy; exchange rate overshooting; forward premium; global vector error correction model; Geldpolitik; Schock; Overshooting; Devisentermingeschäft; Fehlerkorrekturmodell; Schätzung; Industriestaaten